Family Climate, Life Satisfaction, and the Mediating Role of Self-Efficacy among Filipino Adolescents - Sayawan, Cherieville; De Jose, Elmer (Journal of Interdisciplinary Perspectives, 2025)
This predictive correlational study examines the family climate, life satisfaction, and the mediating role of self-efficacy among Filipino adolescents. The study delved into the respondents' perceptions of their social, physical, and emotional relationships with their parents, their subjective evaluation of life, and their belief in their abilities. Through the Family Climate Scale Questionnaire, the Satisfaction with Life Scale, and the General Self-Efficacy Scale, this study uncovered the family climate, life satisfaction, and self-efficacy levels among Filipino adolescents. Moreover, it explores the relationships among these variables, particularly examining the mediating role of self-efficacy. The findings indicated that Family Climate was positively correlated with Life Satisfaction (r = .45, p < 0.001) and Self-Efficacy (r = .33, p < 0.001). Similarly, Self-Efficacy showed a high positive correlation with Life Satisfaction (r = .84, <0.001). The mediation analysis revealed that Self-Efficacy is a significant partial mediator between Family Climate and Life Satisfaction. This is supported by the statistical significance of all relevant paths: path a (Family Climate to Self-Efficacy, β=.48, p < 0.001), path b (Self-Efficacy to Life Satisfaction, β=.39, p < 0.001), and path c (Family Climate to Life Satisfaction after accounting for Self-Efficacy, β=.54, p < 0.001). Overall, this study concludes that family climate influences life satisfaction directly and indirectly through self-efficacy. A positive family climate boosts self-efficacy, contributing to increased life satisfaction. Nonetheless, family climate still exerts a significant direct positive effect on life satisfaction, even when considering the role of self-efficacy.